Representations of Matabeleland and Midlands disturbances through the documentary film Gukurahundi: A moment of Madness(2007) - Rwafa, Urther (Taylor and Francis, 2016)
In the post-independent Zimbabwe, to mention the word ‘Gukurahundi’ is to make a reference to a taboo subject matter. The word ‘Gukurahundi’ invokes profound and bitter memories, torture and murder of more than 20,000 people – mostly of Ndebele origin, in Matabeleland and parts of Midlands. The killings were carried out between 1982 and 1987 by North Korean-trained Fifth Brigade that operated under the auspices of the new government. Gukurahundi: A Moment of Madness (2007) produced by Zenzele Ndebele is a documentary film that memorialises and tells harrowing stories of torture and murder during the times of Gukurahundi. This documentary is also a counter-narrative to monolithic explanations to Gukurahundi atrocities. There is a species of writing that is so narrow that the writing collapses everything to do with the killings to a Shona versus Ndebele dichotomy. In its limitedness, the writing insinuates that all Shona people were involved, and therefore should be made to account for Gukurahundi atrocities. Through Ndelele's documentary, this article contends that this kind of writing is as lethal as Gukurahundi itself because the writing essentialises ‘ethnicity’ and ‘tribal hatred’ as centres of struggle that should dominate the discourses of Gukurahundi.